John Lennon - Conord, Bruce W. (New York : Chelsea House, 1994)
A biography of the famous singer, songwriter, and member of the Beatles.
Includes bibliographical references and index.
Discography : p. 122.
Keywords: Lennon, John, -- 1940-1980 -- Juvenile literature; Lennon, John, -- 1940-1980.; Rock musicians -- Biography -- Juvenile literature; Musicians; Rock music